Pasar Modal Syariah di Indonesia: Tinjauan Prinsip, Mekanisme dan Tantanganya - Oktaviani, Ria; Supriadi, Supriadi; Kamaruddin, Kamaruddin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
This research discusses the development, structure, and challenges of the Islamic capital market in Indonesia as an alternative investment that is in accordance with Islamic principles, such as the prohibition of usury, gharar, and maysir. Using a descriptive qualitative approach and literature review, this research discusses the role of OJK and DSN-MUI. The evaluation focused on sharia compliance as well as financial efficiency in trading and supervisory mechanisms. The results of this study show significant growth thanks to regulatory support, increased public interest, and innovations such as retail sukuk and digital platforms, however, challenges remain, such as low sharia financial literacy, lack of sharia-compliant issuers, and limited qualified human resources. Compared to conventional markets, Islamic capital markets are more ethical, but still have low market share and liquidity. The novelty of this research lies in analyzing the integrity between sharia compliance, regulation, and implementation in a Muslim-populated country. This research also provides an important contribution to the development of inclusive and ethical financial markets, and serves as an example for regulators, industry players, and academics to encourage the sustainable growth of Islamic capital markets.